Abdominal Acupuncture as an Adjunctive Therapy for the Recovery of Motor Function After Stroke: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Zhan, Jie; Xiong, Buhui; Zhang, Peiming; Wang, Yiqiao; Tang, Yuyuan; Zhan, Lechang; Lu, Liming (Frontiers in Neurology, 2021)
Background: Bo's abdominal acupuncture (BAA) is a novel therapy in alternative and complementary medicine and has been frequently used for stroke in recent decades.However, no systematic evidence has been performed to confirm the effect and safety of BAA as an adjunctive therapy for post-stroke motor dysfunction (PSMD). Objectives: This review aimed to assess the efficacy and safety of BAA as an adjunctive therapy for improving motor function and ADL in patients with PSMD. Methods: Seven databases were searched from inception to December 2020: Embase, PubMed, Cochrane Library, CBM, VIP, WAN FANG, and CNKI. All RCTs involving BAA plus another therapy versus the same other therapy alone were identified. The methodological quality of the included trials was assessed according to the Cochrane risk of bias criteria. If more than half of the domains in a study are at low risk of bias, the overall quality of the study is low risk. We conducted a meta-analysis for primary outcomes using a random effects model and performed a narrative summary for the secondary outcome. We also conducted subgroup analysis for primary outcomes based on different add-on treatments to BAA. Results: 21 trials with 1473 patients were included in this review. The overall quality of the 14 included trials was low risk. Meta-analyses indicated that the effect of the BAA group was better than that of the non-EA group on the FMA (WMD 9.53, 95% CI 7.23 to 11.83, P < 0.00001), FMA for upper extremities (WMD 11.08, 95% CI 5.83 to 16.32, P < 0.0001), FMA for lower extremities (WMD 5.57, 95% CI 2.61 to 8.54, P = 0.0002), and MBI (SMD 1.02, 95% CI 0.65 to 1.39, P < 0.00001). Two trials (9.5%) reported BAA-related adverse events, and the most common adverse event was local subcutaneous ecchymosis. Conclusions: BAA as an adjunctive therapy may have clinical benefits for improving motor function and ADL in patients with PSMD. However, our review findings should be interpreted with caution because of the methodological weaknesses in the included trials. High-quality trials are needed to assess the adjunctive role of BAA in patients with PSMD.